2009
DOI: 10.4319/lo.2009.54.5.1574
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of multiannual thermal profiles in deep Lake Geneva: A comparison of one‐dimensional lake models

Abstract: In this study, we report on the ability of four one-dimensional lake models to simulate the water temperature profiles of Lake Geneva, the largest water body in Western Europe, over a 10-yr period from 1996 to 2005, using lake models driven by a common atmospheric forcing. These lake models have already demonstrated their capability of reproducing the temperature distribution in smaller lakes and include one eddy-diffusive lake model, the Hostetler model; a Lagrangian model, the one-dimensional Dynamic Reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 46 publications
4
177
0
1
Order By: Relevance
“…This allowed varying the depth, temperature, and water flow over time. Regarding the objectives of this study, this feature was an additional argument-besides the confirmed reliability of the model [Perroud et al, 2009]-for the choice for this k-epsilon model out of the numerous available lake turbulence models.…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed varying the depth, temperature, and water flow over time. Regarding the objectives of this study, this feature was an additional argument-besides the confirmed reliability of the model [Perroud et al, 2009]-for the choice for this k-epsilon model out of the numerous available lake turbulence models.…”
Section: /2mentioning
confidence: 99%
“…In this study, we used a buoyancy-extended version of the one-dimensional vertical k-epsilon model SIMSTRAT by Goudsmit et al [2002] that was applied to a medium-sized lake by Peeters et al [2002] and has been tested various times since then [Perroud et al, 2009] boundary mixing at the sediment, as well as sinks of k by mixing against the stratification (turbulent diffusivity) and dissipation (epsilon). Details are provided in Goudsmit et al [2002].…”
Section: Lake Model Formulationmentioning
confidence: 99%
“…It has been used at a wide variety of water bodies with different morphologies and climates (e.g. Gal et al, 2003;Perroud et al, 2009;Weinberger and Vetter, 2012). However, most applications of the model have been related to water body ecology or water quality rather than for the specific purpose of LE quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some of the variables can change significantly over the lake surface and in time (e.g., wind), and reconstructing their spatial variation can be a particularly hard task. Predicting water temperature is nonetheless a desired goal and models of different types and of different complexity have been proposed, ranging from simple regression models (Livingstone and Lotter 1998;Sharma et al 2008) to more complex process-based numerical one-dimensional Perroud et al 2009;Thiery et al 2014) and three-dimensional models (Wahl and Peeters 2014).In this work, we aim at obtaining results that are accurate enough to reliably predict the annual cycle of lake surface temperature and its interannual variability, using a simple model that requires a minimum amount of information. In particular, we assume that air temperature is a proxy for the integrated effect of the relevant processes and fluxes (Livingstone and Padisá k 2007) and that can be used as the unique input variable of the model.…”
mentioning
confidence: 99%